The Impact of Journal Self-Citation: The Case of Energy Education Science and Technology - Umut Al; İrem Soydal (Türk Kütüphaneciliği)
The impact of scientific studies is measured and examined quantitatively and qualitatively by bibliometric methods. By means of research evaluation studies, comparisons are made in between countries, institutions or individuals indicate scientific development, and consequently all these efforts help the formation of scientific publication policies of countries and institutions. This study analyzes the journal self-citation concept and its impact on academic publishing. It also examines bibliometric features of the Energy Education Science and Technology that has been indexed by the Science Citation Index Expanded since 2008. In conclusion, it is found that 94% of the Energy Education Science and Technology citations are journal self-citation. Self-citation numbers that affect the increase of EEST’s impact factor lead to serious abnormities and cause unethical consequences.